Nurturing Critical Consciousness through Faith: Integrating Fitrah-Based Education in the Transformation of Islamic Early Childhood Education - Ajeng Satiti Ayuningtyas Okta Ferdiana (SEA-CECCEP, 2025)
Abstract— Early childhood Islamic education is important because it influences children’s spirituality, character, and worldview. However, in practice, many early childhood education institutions in Islamic countries are still oriented towards a memorization and dogmatic approach, which provides little space for the development of children’s critical thinking from an early age. This article aims to examine the integration of a fitrah-based education approach in transforming early childhood Islamic education, with a focus on its potential to foster critical awareness rooted in faith. This study employs a qualitative method, drawing on literature reviews, a case study, and interviews with the management and a teacher of the BATAS Study. This early childhood education institution implements a fitrah-based education approach. The results of the study show that education based on fitrah can encourage children to think reflectively, understand values contextually, and internalize Islamic spirituality meaningfully. The main challenges include changing the role of teachers from being full authorities in learning to facilitators and nurturers of the child’s maximum potential. The BATAS Study offers a real-life example of how integrating faith, freedom of thought, and emotional guidance can shape children into independent, empathetic, and socially aware individuals. This article recommends a more transformative and dialogical approach to Islamic education, one that humanizes children from an early age, aligning with their inherent nature.